Medication with caution: Analysis of adverse reactions caused by a combination of Chinese medicine and warfarin sodium tablets. (23rd May 2020) - Zhuang, Wei; Sun, Ge; Lin, Xiaolan; Chen, Bin; Wu, Li; Jiang, Dechun; Xi, Shengyan
Abstract: Ethnopharmacological relevance: With the extensive recent use of warfarin and traditional Chinese medicine (TCM) in combination, TCM has been found to affect warfarin's pharmacokinetic and pharmacodynamic parameters. Warfarin is a widely used oral anticoagulant, which has a narrow therapeutic window and a high likelihood of interacting with other drugs and resulting in serious adverse reactions. Contrary to widespread public expectations, TCM, despite being natural, is not always safe. Aim of the study: To report the adverse drug reactions (ADR) resulting from the use of Chinese medicine and warfarin sodium tablets in combination. Methods: According to a hospital ADR monitoring report, we collected data on four clinical cases involving warfarin and single Chinese herbal medicine, warfarin and proprietary traditional Chinese medicine product, warfarin and Chinese medicinal injection, and warfarin and compound decoction. The Naranjo ADR score evaluation scale was used to analyze the relationships between warfarin and Chinese medicines. Results: Fluctuations in the international normalized ratio (INR) were accompanied by bleeding in some patients who regularly and simultaneously utilized warfarin and Chinese medicine. The potential risk of bleeding due to the interaction between TCM and warfarin is easily and often overlooked by both Western and TCM doctors. Conclusions: Warfarin in combination with different traditional Chinese herbal medicines poses risks of INR fluctuations and adverse reactions such as bleeding. In the future, the safety awareness regarding reasonable administration of warfarin and herbal medicine should be emphasized. Graphical abstract: Image 1